2017
DOI: 10.1210/jc.2017-01187
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Stored in Fat Tissue During a 5-Year Intervention Affects Serum 25-Hydroxyvitamin D Levels the Following Year

Abstract: Vitamin D and 25(OH)D stored in adipose tissue after 3 to 5 years of vitamin D supplementation may have a clinically relevant effect on serum 25(OH)D level the following year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…There was a negative trend in serum 25(OH)D concentrations that was fastest in the first 3 months and yielded a half-life of 83 days. The half-life of serum 25(OH)D thereafter was 255 days, indicating a much slower decrease of 25(OH)D after the first 3 months (27). A similar pattern of elimination was demonstrated in our dog where serum 25(OH)D concentrations substantially decreased in the first 4 months and then proceeded to gradually decrease thereafter.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There was a negative trend in serum 25(OH)D concentrations that was fastest in the first 3 months and yielded a half-life of 83 days. The half-life of serum 25(OH)D thereafter was 255 days, indicating a much slower decrease of 25(OH)D after the first 3 months (27). A similar pattern of elimination was demonstrated in our dog where serum 25(OH)D concentrations substantially decreased in the first 4 months and then proceeded to gradually decrease thereafter.…”
Section: Discussionsupporting
confidence: 85%
“…However, even this tightly regulated negative feedback system can be circumvented by markedly increased 25(OH)D concentrations, which can activate vitamin D receptors as well as displace calcitriol from its carrier protein resulting in excessive "free" calcitriol concentrations (24)(25)(26). The reported half-life of serum 25(OH)D following cholecalciferol rodenticide toxicosis is variable and likely longer than reported in the veterinary literature, as demonstrated by a recent human study that examined vitamin D storage following administration of oral cholecalciferol for 5 years (27). Interestingly, that study identified that the serum half-life of 25(OH)D and thus rate of elimination varied with time.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of time spent in the sun shown to be beneficial may be such that sufficient amounts of vitamin D are created for storage and release during the winter, when temperatures and low UVB radiation availability make vitamin D production impossible-such as at northern latitudes. Previous research has shown vitamin D produced as a result of solar UVR exposure can be stored in adipose tissue and released during times of vitamin D insufficiency (Martinaityte et al 2017). The lack of a greater protective effect with higher sun exposure may also be influenced by a sublinear relationship between sun exposure and dermal synthesis of vitamin D (Nair-Shalliker et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Supplementing with 20 000 international units (IU) of vitamin D 3 per week for 3-5 years leads to a substantial increase in vitamin D 3 content in subcutaneous abdominal adipose tissue, approximately sixfold greater than placebo (Didriksen et al 2015). The amount of 25(OH)D present in adipose explants remained correlated with serum 25(OH)D concentrations 1 year after supplementation had ceased (Martinaityte et al 2017). Although it is worth noting that values for serum 25(OH)D and adipose tissue vitamin D 3 measured in this study varied considerably between participants, which may be explained by the fourfold variation in body fat mass across the study population.…”
Section: Vitamin D Accumulation In Adiposementioning
confidence: 99%